2020
DOI: 10.20546/ijcmas.2020.910.394
|View full text |Cite
|
Sign up to set email alerts
|

Biosensors and Bioremediation as Biotechnological Tools for Environmental Monitoring and Protection

Abstract: Environmental biotechnology is the integration of natural sciences and engineering in order to achieve the application of organisms, cells, parts thereof and molecular analogues for the protection and restoration of the quality of our environment. Biotechnological processes to protect the environment have been used for almost a century now, even longer than the term "biotechnology" exists. Biotechnological techniques to treat waste before or after it has been brought into the environment are components of envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…The standard solution of carbaryl was freshly prepared in at least 5 concentrations (0.02–20.0 mg L −1 ), and the standard solution of 1-naphthol was fresh-prepared in at least 5 concentrations (0.005–2.0 mg L −1 ). The procedure of carbaryl and 1-naphthol determination was modified by Biswas and colleagues and Ozhan and colleagues [ 8 , 16 ]. Plant samples were cut and separated into shoots and roots, weighed, and the weights were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard solution of carbaryl was freshly prepared in at least 5 concentrations (0.02–20.0 mg L −1 ), and the standard solution of 1-naphthol was fresh-prepared in at least 5 concentrations (0.005–2.0 mg L −1 ). The procedure of carbaryl and 1-naphthol determination was modified by Biswas and colleagues and Ozhan and colleagues [ 8 , 16 ]. Plant samples were cut and separated into shoots and roots, weighed, and the weights were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The removal efficiency of several plants has been reported regarding pesticides, such as carbofuran, chlorpyrifos, carbaryl, inuron, permethrin, and triazophos [ 3 , 11 , 12 , 13 ]. Some species, such as Phragmites sp., can remove pesticides [ 14 , 15 , 16 ], while plants, such as Phragmites australis , have been used to remove pesticide wastewater based on a wetland system [ 14 , 17 ]. Among these remediating plants, some can be classified as ornamental and leguminous, such as lupine, sunflower, and morning glory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Op De Beeck et al, 2015) and Funneliformis mosseaewas (Berthelot et al, 2018) plant biomass with Cd were also treated utilising biodegradation process. Bano et al (2020) and Jing et al (2020) observed that the degradation process of plant biomass is more effective with fungi than bacteria. Following that, Zhang et al (2013) and Chen et al (2016Chen et al ( , 2018 reported on the effective degradation of plant biomass by utilising fungi.…”
Section: Anaerobic Digestion and Microbial Degradationmentioning
confidence: 99%